PEEL WITH A LOW GLYCEMIC INDEX FOR ALTERNATIVE FOOD FOR DIABETES MELLITUS) - Firdaus; Aorama, Aulia; Nadya, Salshabila; Milla, Viona Izzatul (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2025)
Diabetes is a chronic disease that can occur if the body is unable to use the insulin it produces effectively. People with diabetes have special dietary arrangements that are different from non-diabetic people. One of them is by consuming foods with a low glycemic index. Cassava peel has good potential for development. Artificial rice from cassava peel waste, besides having good nutritional content, is also very minimally used, especially in the city of Padang. This research aims to develop analog rice from cassava peel waste, which has the potential to have a low glycemic index and be an alternative food for people with diabetes. The method of this research is that this research uses an experimental test method using a randomized design comparing cassava peel flour and sago starch flour with the ratio F1(60:40), F2(70:30), and F3(80:20). Organoleptic tests were carried out on 30 semi-trained panelists. Data analysis used software with the Kruskal Wallis and Mann Whitney tests at a 5% level. The Glycemic Index test was carried out by taking blood using a finger prick test or glucometer at 0, 30, 60, 90, and 120 minutes. Results: From organoleptic and proximate testing, the best formulation was obtained, namely F3(80:20). The nutritional content of this formulation is 3.51% ash content; fat content 6.3%; protein content 1.64%; carbohydrates 81.16%; amylose 16.47%; crude fiber 6.07%; dietary fiber 29.14%. The glycemic index result was 20.63. Artificial rice from cassava skin has a low glycemic index, so it has the potential as a food for diabetes mellitus.